Phenolic profile and antioxidant activity from wild and in vitro cultivated Rhynchostele rossii (Orchidaceae) - Martínez Cruz, Nieves del Socorro; Monribot Villanueva, Juan Luis; Cocotle Ronzón, Yolanda; Gutiérrez Sánchez, Rosa Angélica; Guerrero Analco, José Antonio (Instituto de Ecología, A.C., 2020)
Background and Aims: Rhynchostele rossii is an orchid native to Mexico known as gallinitas (little chickens) that is threatened due to overexploitation for ornamental purposes, as a consequence of which it is necessary to realize efforts for its conservation. To date there are no reports of phytochemical studies of this orchid, although it is well known that species of the Orchidaceae family are a good source of bioactive and nutraceutical compounds (e. g. vanillin). Therefore, the main objective of this research was to establish a R. rossii in vitro germination protocol for propagation and determination of phenolic compounds that contribute to its phytochemical knowledge.Methods: A specimen of a wild plant and some seedlings obtained by in vitro culture were dried, milled and their components extracted with MeOH; anti-free radical activity (DPPH), total phenols and flavonoids were determined by spectrophotometric methods, and individual phenolic compounds were identified and quantified by liquid chromatography coupled to mass spectrometry (LC-MS).Key results: The root of the wild plant showed the highest content of total phenols and flavonoids with 121.60 mg GAE g-1 and 108.73 mg CE g-1, respectively, and the best anti-free radical activity with an IC50 53.63 μg ml-1. Extracts from seedlings obtained by in vitro culture also produced phenolic compounds, showing a total phenolic and flavonoid content of 37.35 mg GAE g-1 and 0.16 mg CE g-1, respectively. One coumarin (scopoletin) , three cinnamic acids (4-coumaric acid, ferulic acid and trans-cinnamic acid), three benzoic acids (vanillic acid, vanillin and 4-hydroxybenzoic acid) and three flavonoids (quercetin-3-D-galactoside, quercetin-3-glucoside and kaempferide) were identified and quantified by LC-MS.Conclusions: This study demonstrates that R. rossii is a potential source of antioxidant metabolites that can be obtained by in vitro culture, without harming the wild specimens.